2009
DOI: 10.1016/j.ejcts.2009.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve lobectomy for patients with non-small-cell lung cancer: a simplified approach

Abstract: Sleeve lobectomy for lung cancer, although technically demanding, is associated with low morbidity and mortality and satisfactory immediate and long-term results. With increasing experience, more lung-sparing procedures should be performed in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
3
0
2
Order By: Relevance
“…17. In accordance with the reported results from the literature we can also conclude, the bronchial and vascular sleeve lobectomy can be performed safely, and is a good alternative solution to avoid pneumonectomy (Konstantinou et al, 2009;Ludwig et al, 2005). As shown in our study, selected patients with central lung metastases can be also included for this procedure after fulfilling the standard criteria for pulmonary metastasectomy.…”
Section: Resultssupporting
confidence: 89%
“…17. In accordance with the reported results from the literature we can also conclude, the bronchial and vascular sleeve lobectomy can be performed safely, and is a good alternative solution to avoid pneumonectomy (Konstantinou et al, 2009;Ludwig et al, 2005). As shown in our study, selected patients with central lung metastases can be also included for this procedure after fulfilling the standard criteria for pulmonary metastasectomy.…”
Section: Resultssupporting
confidence: 89%
“…In their series of 100 patients, Kutlu and Goldstraw [20] avoided the wrapping of the bronchial anastomosis and concluded that the careful handling of the airway, with the preservation of as much peribronchial tissue as possible, can avoid the need of any tissue flap on the bronchial anastomosis. Konstantinou et al [21] routinely did not perform any wrapping of the bronchial anastomosis and registered no anastomotic complication. Accordingly, Rea et al [22] did not find any significant difference in 30-day mortality between patients with or without pedicled flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Other long series describing the results of SL or comparing SL and PN results have been published (Table 6) [4,5,7,9,15,16,19,[22][23][24][25]. The series frequently lasted for decades, as broncho-angioplastic techniques were developed in these centres.…”
Section: Commentmentioning
confidence: 96%